Nike : tiptoeing into the metaverse - Sawhney, Mohanbir S., (SAGE business cases., 2022)
Throughout 2021, excitement about the metaverse as the next generation of the internet experience had been building steadily. The buzz reached a fever pitch in October 2021, when the CEO of Facebook, Mark Zuckerberg, announced that the company was changing its name to Meta and that it would spend $10 billion to build "the metaverse." Nike had been exploring opportunities in this new virtual environment with several experimental probes, including its purchase of a virtual sneaker company called RTFKT, partnerships with game platforms Roblox and Fortnite, the creation of blockchain-based digital sneakers called CryptoKicks, and moves to protect its brands and logos by filing for trademarks for its virtual sneakers and logos. In its early metaverse initiatives, Nike had employed a "probe and learn" strategy to evaluate the metaverse as a new channel for customer engagement and to create new digital revenue streams. However, it was now time for Nike to define a cohesive metaverse strategy that would help drive its business goals. To do this, Nike's digital team needed to understand how each of the metaverse initiatives would help Nike to grow revenue, build brands, and promote its thought-leadership position as an innovator. The team then needed to prioritize these initiatives by assessing their risks, rewards, and reversibility. Finally, it needed to define a roadmap to scale and enhance each initiative. In charting its course in the metaverse, Nike also needed to consider whether the timing was right to place big bets on metaverse platforms and assets, given the high level of uncertainty about the evolution of this emerging space.